The Strategy of the Indonesian Government in Implementing the Wonderful Indonesia Digital Diplomacy Program - Muhammad Fahrizal; Rio Sundari; Muhammad Arsy Ash Shiddiqi; Faisyal Rani (Kemudi, 2022)
This paper analyzes the strategy of the Indonesian government in implementing the Wonderful Indonesia digital diplomacy program. This paper is analyzed using the concepts of digital diplomacy, multitrack diplomacy, and nation branding. The selection of these three concepts is due to the existence of Wonderful Indonesia as a tagline for Indonesian tourism branding which can be categorized as part of Indonesia's soft diplomacy. Meanwhile, the Indonesian government's strategies to attract foreign tourists were carried out by involving several shareholders which were in line with the concept of multitrack diplomacy. This research uses descriptive qualitative method or literature study. The purpose of this study is to analyze the strategy of the Indonesian government in promoting Indonesian tourism through digital diplomacy. This research provides an overview of Wonderful Indonesia and its marketing through digital media and other media and communications and ensures that Indonesia's tourism developments in 2011, 2013, 2015, 2017, and 2019. Based on the research results, it can be said that the Indonesian government, especially the Indonesian Ministry of Tourism and Creative Economy, by utilizing digital media as a means of diplomacy is considered to be time efficient and able to reach the market and echo the Wonderful Indonesia promotional message in the international sphere.